Maize-bean intercropping system during the off-season - Ramalho, Magno Antônio Patto; Coelho, Antônio Marcos; Teixeira, Antônio Lisboa Santos (Pesquisa Agropecuaria Brasileira, 2014)
Aiming at maize (Zea mays L.) production in association with beans (Phaseolus vulgaris L.), different planting times within the off-season were evaluated at Centro Nacional de Pesquisa de Milho e Sorgo (National Maize and Sorghum Research Center), in the State of Minas Gerais, Brazil, in 1982 and 1983. In each period, a different experience was carried out, in a randomized blocks with two replications and six treatments. Two maize varieties (BR 126 and BR 105) were used for the experiments, along with the bean varieties CNF 010 and Rio Tibagi. Besides intercropping with beans, each maize variety was planted apart. The experiments were carried on between February and May, with three periods in 1982 and four periods in 1983. Besides the production of commercial roasting ear and dry bean grains, the dry matter production from both maize and bean was evaluated. The results showed that good roasting ear production is possible, mainly in February and March plantings. A 20% reduction of commercial roasting ear and maize dry matter resulted from the intercroppings. Therefore, maize-bean intercropping for these periods will hardly result economically successful. There was no influence of the several bean and maize varieties over the intercroppings efficiency.